Pengaruh Pemberian Ekstrak Tempe TErhadap Kadar Ureum dan Kreatinin Ginjal Tikus Putih Jantan Galur Wistar (Rattus Norvegicus) Dengan Pemberian Paracetamol Dosis Toksik - Dewi Marlina (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2012)
Background: Tempe contained 6,7,4-trihydroxy isoflavone antioxidant that has the most powerful antioxidant properties as compared to isoflavones in soy, which may counteract free radicals and reduce the formation of NAPQI (N-acetyl-Parabenzoquinoneimine) resulting from the metabolism of paracetamol. This study was to determine the effect of tempe extract on levels of urea and creatinine renal wistar strain male white rats (Rattus norvegicus) by administering toxic dose of paracetamol. Methods: An experimental laboratory with controlled group post test only design. Test animals used were male white rats of wistar strain (Rattus norvegicus), aged 2.5 months with a weight of 180-200 grams, a total of 30 individuals. Subjectswere divided into 5 groups by randomization group and each group of subjects consisted of 6 male mice. The first group was the control group were given distilled water and NaCMC and the other group is the treatment group were given a dose of tempe extract 160, 320 and 640mg/kgBB for 14 days. In all groups at days 12, 13, and 14 are given toxic doses of paracetamol. On day 15 blood sampling done through the heart of male white rats. Parameter measurements is elevated levels of urea and creatinine rat kidney cells. Analysis of the data in the form of urea and serum creatinine levels were statistically analyzed by t-tests, analysis of variance and Pearson correlation one way with a significance level of p <0.05. Results: The results showed that the tempe extract at a dose of 160 and 320mg/kgBB for 14 days by administering toxic dose of paracetamol 900mg/kgBB on day 12, 13 and 14, leading to increased levels of urea and creatinine levels, while the tempe extract at a dose 640mg/kgBB not lead to increased levels of urea and creatinine compared with the treatment group before treatment. Conclusion: Tempe extract can prevent damage to kidney function of white male Wistar rats (Rattus norvegicus), which follows the pattern dependent manner.